STRATEGI PENGEMBANGAN KOMPETENSI PEDAGOGIK GURU RUMPUN PAI DI MTS. MU’ALLIMINISLAMIYAH KABUPATEN MUSI BANYUASIN - Sutarmizi Sutarmizi; Syarnubi Syarnubi (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
This study was to analyze the Pedagogical Competency Development Strategy for PAI Cluster Teachers in MTs. Mu'allimin Islamiyah, Musi Banyuasin Regency, includes strategies for developing pedagogic competence and what factors influence it.The type of qualitative research is to inform the principal, and teacher of the PAI family. The method of collecting data is an interviews, observation, and documentation. Non-statistical qualitative data analysis techniques with descriptive analysis as data presentation are collection, reduction, display, verification, and triangulation.The results of this study indicate the development of the pedagogic competence of PAI cluster teachers in MTs. Mu'allimin Islamiyah Musi Banyuasin Regency on aspect 1). Understanding, mastering students, teachers developing dialogical communication between students, recognizing the stages of development and individual differences both morally, intellectually and the potential of students. 2). By mastering theories and principles, and learning, teachers develop varied teaching techniques and motivate students with reciprocal responses and stimuli. 3). In curriculum development, teachers can formulate, compile, organize, and design learning planning programs, and use media and learning models by utilizing information and communication technology media. 4). The development of the potential of student teachers can direct students to take part in extracurricular activities, OSIS. Amtrak, arts and culture, social services with the aim of activity and creativity, thinking skills, identifying interests and talents facilitate students to develop academic and non-academic potential. 5). In the development of educational learning activities, teachers have been able to pay attention to the level of needs, environment, opportunity, intellectuality, spirituality, psychological and emotional students by applying skills.